«THE MYTH OF GALICIA» BY LEOPOLD VON SACHER-MASOCH AS THE SITUATION OF ETHNO-CULTURAL BORDERLANDS - Сав’юк, А. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the phenomenon of Galicia in the prose of Zaher von Masoch. It is proved that the models of coexistence of ethnic cultures in the dimension of the multifaceted heterogeneity of Galicia are based on the principle of mythological universality, idyllism and general stereotyped pattern. Galicia’s macrocosm serves as the tige of cultural diversity of the "small homelands" of the Habsburg world, which are depicted in the context of a non-conflict dialogue of cultures and religions.